1989
DOI: 10.1007/bf02774183
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin receptors in the human gastrointestinal tract and pancreas

Abstract: The specific binding of 125I-labeled gastrin-17 was studied in samples of human gastric mucosa, duodenal mucosa, colonic mucosa or pancreatic tissue obtained surgically. With regard to gastric fundic mucosa, the criteria for receptor binding were studied, and saturability, high affinity, tissue specificity and hormone specificity were demonstrated. The dissociation constant for gastric fundic mucosa was 1.6 X 10(-9)M, and the binding capacity was 15 fmol/mg protein. Tissue specificity studies revealed a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Gastrin is known to be an important gut‐related hormone and a growth factor for gastric cancer cells 21 , 22 and gastric tumour cells have been shown to contain its receptor. Reports have indicated that, after eradication therapy of H. pylori , a decreased level of several cytokines such as interleukin (IL)‐1, IL‐2, tumour necrosis factor‐ α and interferon‐ γ , in the gastric mucosa as well as increased acid output results in the decreased level of serum gastrin 23, 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrin is known to be an important gut‐related hormone and a growth factor for gastric cancer cells 21 , 22 and gastric tumour cells have been shown to contain its receptor. Reports have indicated that, after eradication therapy of H. pylori , a decreased level of several cytokines such as interleukin (IL)‐1, IL‐2, tumour necrosis factor‐ α and interferon‐ γ , in the gastric mucosa as well as increased acid output results in the decreased level of serum gastrin 23, 24 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown with an 125 I-labeled gastrin-binding assay that GR is present in the human gastric corpus [8]. To date, many studies have revealed the localization of GR in the human stomach.…”
Section: Introductionmentioning
confidence: 99%
“…The EC 50 was 28 6 5 nM, and the K D of hG17 for the CCK-B receptor in these cells was 17 6 3.5 nM. Due to the level of receptor expression, the binding data presumably reflects the low-affinity state of the receptor as the reported highaffinity dissociation constant of 125 I-hG17 is on the order 1.6 3 10 29 M. 35 Figure 1 shows that 10 nM hG17 produces noticeable plasma membrane arrestin-GFP redistribution even after 5 min. After a 30-60 min exposure of the cells to hG17, endosomes containing arrestin-GFP become visible (compare Fig.…”
Section: Characterization Of Gastrin Binding and Signalingmentioning
confidence: 95%